Computer Communication Networks Security Analysis - Gumel, Lawan Ahmed (1999)
We are living in the "Information Revolution", where development of powerful communication systems and digital technologies have resulted in the buildup of massive information banks by government, industries and even individuals, which are required to be protected to maintain privacy, confidentiality, availability and integrity of national and commercial information. It has also allowed for automation of services and such systems must protect customers against modern day "electronic crimes". The first part of this thesis is a study into the aspect of the development of secure communication between group of entities. The thesis gives an overview of the general issues that are raised by the concept of cryptosystems, followed by discussions on the methods currently available for the conduct of such techniques. Generic categories of threats and vulnerabilities to computer networks are outlined as well as network security objectives. The study culminates in the description of a recommended alternative approach for the development of Group Oriented Cryptosystems (GOC) which can be used to solve the problem of entity authentication and subsequent key distribution in order to enhance multiple-entity (group of entities) communications with confidentiality and integrity services.E-mail security is about protecting electronic mails from spies, interlopers, and spoofs. People who may want to destroy, alter, or just look at our private communications. The second part of the thesis shows how we can protect the financial information, contract negotiations, or personal correspondence we entrust to public or private networks by means of Digital Envelop. Furthermore, the model developed can be practically implemented.